Field reports, Ann Johnson, spring 1991 - Johnson, Annet al (1991)
Field reports with detail about some sightings as well as a note about the weather and season submitted by Ann Johnson for spring 1991. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1991. Epson - sheet feed